(3GdESJQGJjLjGJ(B-(3GdegGQGJ hGdCSGdjHs - (3aGdjQj(B, (3QhO HdGfJjfs (((3O(B.(3e(B):s (3OGQ GdJbOe GdYdej(B,s, 2006)
(3GdeaGhVGJ(B-(3GdeaGhVGJ hGdEOQGc(B-(3GdTNUjI hGdSdhc aj GdYedjI GdJaGhVjI(B-(3GdfRGY CSHGHg hGfYcGSGJg(B-(3BdjI GdJaGhV hafhfg(B-(3GdJMGdas
Keywords: (3BdjI GdJaGhVs; (3GdJMGdas; (3GdeaGhVGJs; (3GdfRGYs; (3eaGhVGJ GdEOQGcs